The Rise of Q-Commerce: Transforming Retail and Logistics - Pandey, Nandlal (Management Journal for Advanced Research, 2025)
The retail landscape is undergoing a seismic shift with the emergence of Q-Commerce (Quick Commerce), a paradigm that promises to revolutionise the way we shop and receive goods. Q-Commerce leverages cutting-edge technology, ultra-fast delivery models, and data-driven insights to deliver products to customers in record time, often within minutes. E-commerce can make delivery faster and more efficient, especially for perishable goods like fruits, veggies, and some medicines that don't last long. The pandemic accelerated the shift to online shopping, setting a new standard for convenience that's tough for traditional retail to match. Q-commerce relies on tech, using AI, real-time data, and better logistics to deliver superfast. The present study explores the rise of Q-Commerce, its impact on traditional retail and logistics, and the opportunities and challenges it presents. Evolution of Q-Commerce and its key players. Disruption of traditional retail models and supply chains. This study also tried to find out whether consumer satisfaction grew with the limited introduction of e-commerce in certain areas of online businesses and concluded that the satisfaction level did increase to some extent. Innovations in logistics and last-mile delivery: Opportunities for growth and challenges ahead. As Q-Commerce continues to reshape the retail landscape, businesses must adapt to stay ahead. This abstract sets the stage for a deeper dive into the world of Q-Commerce and its far-reaching implications.